A Review: Prospective study of non-timber forest product uses in three Meranti species (Shorea spp.). Issue 1 (November 2021) - Wardani, M; Denny,; Susilo, A
Abstract: Meranti ( Shorea spp.) is a commercial timber tree species of Indonesian forest potentially to be developed for Non-Timber Forest Products (NTFPs). We explored the NTFPs perspective of three Meranti species, Shorea hopeifolia (F.Heim) Symington, Shorea ovalis (Korth.) Blume, and Shorea balangeran Burk, by identifying the content of phytochemical compounds. Data collection methods include: exploration, identification to obtain the accuracy of the species scientific name, and analysis the phytochemical content using Gas Chromatographic Mass Spectrometer (GCMS) pyrolysis. We revealed the bark of the tree species contained phytochemical compounds potential for medicinal ingredients especially for antidiabetic, antioxidant, and anticancer. Since the exploitation of the bark is better than the trees, the potential use of non-timber forest products of the meranti supports the conservation of the species. Further research to unveil other benefits of the meranti species should be conducted.